Association of 10-Year C-Reactive Protein Trajectories With Markers of Healthy Aging: Findings From the English Longitudinal Study of Aging. (15th February 2018) - Lassale, Camille; Batty, G David; Steptoe, Andrew; Cadar, Dorina; Akbaraly, Tasnime N; Kivimäki, Mika; Zaninotto, Paola
Abstract: Background: Elevated systematic inflammation is a hallmark of aging, but the association of long-term inflammation trajectories with subsequent aging phenotypes has been little examined. We assessed inflammatory marker C-reactive protein (CRP) repeatedly over time and examined whether long-term changes predicted aging outcomes. Methods: A total of 2, 437 men and women aged 47–87 years at baseline (1998–2001) who were participants in the English Longitudinal Study of Ageing had CRP measured on two or three occasions between 1998 and 2009. Inflammation trajectories were computed using latent-class growth mixture modeling and were related to aging outcomes measured in 2012/2013: physical functioning, cardiometabolic, respiratory, mental health, and a composite "healthy aging" outcome. Results: Four CRP trajectories were identified as follows: "stable-low" (71 per cent of the sample) with baseline mean 1.33 mg/L remaining <3 mg/L; "medium-to-high" (14 per cent) with baseline 2.7 mg/L rising to 5.3 mg/L; "high-to-medium" (10 per cent) with baseline 6.6 mg/L decreasing to 2.4 mg/L; and "stable-high" (5 per cent) with levels from 5.7 to 7.5 mg/L. Relative to the stable-low trajectory, individuals in the medium-to-high had a higher risk of limitations in basic activities of daily living (ADL, odds ratio; 95% confidence interval: 2.09; 1.51, 2.88), instrumental ADL (1.62; 1.15, 2.30), impaired balance (1.59; 1.20, 2.11) and walking speed (1.61; 1.15, 2.24), arthritis (1.55; 1.16, 2.06), hypertension (1.57; 1.21, 2.04), obesity (1.95; 1.36, 2.80), poor respiratory function (1.84; 1.36, 2.50), and depression (1.55; 1.13, 2.12). A lower odds of healthy aging was observed in people in the medium-to-high (0.57; 0.40, 0.79) and stable-high (0.50; 0.27, 0.91) trajectories. Conclusions: Older people who displayed an elevation in CRP levels over a decade experienced an increased risk of adverse aging outcomes.